On the Status of Linguistic Evidence in Litigation - Kredens, Krzysztof (SORUS S.C. Wydawnictwo i Drukarnia Cyfrowa, 2006)
The author discusses the status of expert linguistic evidence in common law systems of England and the USA. Then he touches upon the issue of linguistic evidence in Poland. It is concluded that the scientific validity of expert evidence is only one of the determinants of its legal status. It appears that the status of linguistic evidence in the legal setting is simultaneously conditioned by factors other than the scientific actuality of expert findings.

Autor omawia status dowodów z opinii językoznawcy w systemie prawnym common law w Anglii i USA. Następnie przedstawia kwestię dowodów z opinii językoznawcy w Polsce. Wysuwa wniosek, że naukowe znaczenie takich dowodów jest tylko jednym z determinantów jego znaczenia prawnego. Wydaje się, iż znaczenie dowodów z opinii językoznawcy w kontekście prawnym jest jednocześnie uwarunkowane czynnikami innymi niż faktyczny stan rzeczy ustalony przez biegłego.
Keywords: Lingustic evidence; Forensic lingustics; Expert and linguistic evidence in common law systems